Stress 3Ps and the Health Conditions of Lecturers in Tertiary Institution in Nigeria - Victoria Agunanne; Annabel Obinna-Akakuru; Olachi Oparanozie; Jacinta Achonu (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study examined stress 3Ps (Physical, Psychological and Psycho-Social) as factors on health conditions of lecturers in Imo State. Nigeria. Three specific purposes, three research questions and three hypotheses guided the work. The study employed inferential survey research design. The population of this study consisted of all lecturers in the tertiary institutions in Imo state which are eight thousand, three hundred (8,300). The sample size for this is 382, determined using Taro Yamane formula. The researcher applied random sampling technique to ensure that all selected groups have an equal chance with the other sample that is not selected. The instrument for data collection is a structured questionnaire tagged “Stress 3Ps as factors on health conditions of Lecturers’’. The validity of the research instrument was determined by two specialists in Health Education and one specialist in Educational Measurement and Evaluation, from Alvan Ikoku FCE Owerri and Imo State University Owerri, respectively, while the reliability coefficient over time of the instrument for data collection was established through test retest method of Pearson product moment correlation coefficient (PPMCC) statistics which gave a reliability coefficient of 0.94. The research questions were answered using, mean, and standard deviations presented in tables, while the hypotheses was tested using t-test statistics at 0.05 level of significance. Findings in the course of this study indicated that lecturers exposed to hectic academic activity will experience stress; physical stress affects the mental state of lecturers reducing their level of productivity; psychological stress limits the emotional stability of lectures and directly affects their health condition; psychosocial stress interferes in the intrapersonal and interpersonal relationship of lectures leading to withdrawal and health instability. This study therefore recommends that seminars, workshops and conferences on occupational health services, should be organized periodically for lecturers so as to improve their knowledge on occupational stress and related issues. Also, Lecturers should be encouraged to participate in sport, exercise and fitness programmes in other to maintain a good health status.